The implementation of MS1184:2002 in hypermarket toilet / Farhanis Othman - Othman, Farhanis (Faculty of Architecture, Planning and Surveying, 2010)
The preparation of this dissertation was mainly motivated by the desire to provide an overview of facilities for disable toilet in hypermarket especially at Klang Valley. These are intended to establish the good practice of Malaysian Standard to be adopted in the facility management of disable toilet at hypermarket. The study has specific aim and objectives to achieve in the end. The primary aim of this study is to highlight guideline and standard of Malaysian Standards (MS 1184:2002) in hypermarket. Second objective is to examine the confirmation of Malaysian Standard (MSI 184:2002) in case study examples and the third is to understand the responsibilities of Local Authorities for the disable person’s facilities at hypermarket especially in the design stages or planning approval for new development projects. For the next objective is to measure the satisfaction level of disable person on that facilities and to propose recommendation for better living environment in the life cycle for disable person especially at public toilet. This dissertation includes the outlines of the introduction to the subjects and each sub topic, and also explained elaborate about the facilities for disable persons ami responsible body in Malaysia, statistic of disable persons and also standard facilities in Malaysia. Research methodology which had been applied in the eight (8) case studies is through observations, inspection to element and interviewing relates person of that issues. Then analysis and comparison between case studies due with guideline Malaysian Standard (MS 1184:2002) to ensure which are comply or not. Finally, conclusion from the research findings and development of recommendations for future improvement of disable toilet facilities